Improving Governance and Fighting Corruption in the Baltic and CIS Countries : The Role of the IMF - Gurgen, Emine (Economic Issues; Economic Issues ;, 2000)
Drawing on recent examples of corruptionin the Baltics and former Soviet Union, this pamphlet analyzes the links between governance and corruption, and emphasizes the high economic cost that corruption exacts. The pamphlet outlines how the IMF is working with the countries of the former Soviet Union to curb corruption and put in place the regulatory and legal changes needed to support good government.